Tight Sandstone Gas Reservoir Types and Formation Mechanisms in the Second Member of the Xujiahe Formation in the Anyue Area, Sichuan Basin - Lin Jiang; Xuezhen Sun; Dongxia Chen; Wenzhi Lei; Hanxuan Yang; Yani Deng; Zhenhua Wang; Chenghai Li; Tian Liu; Chao Geng; Tian Gao; Zhipeng Ou (Energies)
With the advancement of oil and gas exploration and development, tight sandstone gas has become a major current exploration field. However, the effective development of tight sandstone gas faces significant challenges due to the strong heterogeneity of tight sandstone reservoirs, diverse reservoir types, complex pore structures, and unclear understanding of reservoir formation mechanisms, which brings great difficulties. Clarifying the types and formation mechanisms of tight sandstone reservoirs is vital for guiding oil and gas exploration and development. This study investigates the characteristics, types, and formation mechanisms of tight sandstone gas reservoirs in the Xujiahe Formation (T3X2) of the Anyue area using core observation, cast thin-section identification, scanning electron microscopy, high pressure mercury intrusion, nuclear magnetic resonance, and other experimental methods. It defines the physical property lower limit of T3X2 reservoirs in Anyue, classifies reservoir types, elaborates on the basic characteristics of each type, and analyzes their genetic mechanisms. The results show that T3X2 reservoirs in the Anyue area can be divided into four types. Sedimentary, diagenetic, and tectonic processes are identified as the primary factors controlling reservoir quality, governing the formation mechanisms of different reservoir types. Based on these findings, a reservoir formation mechanism model for T3X2 reservoirs in the Anyue area is established, providing an important basis for subsequent oil and gas exploration and development in the region.